Water and sanitation : economic and sociological perspectives - Bourne, Peter G. (Academic Press, Inc., 1984)
REFERENCES; Chapter 8. Technology Choices for the Decade; ROLE AND PLACE OF TECHNOLOGY; FASTER PROGRESS NEEDED; BETTER CONTINUITY; CONSUMERS' ACCEPTANCE; ISSUES IN THE CHOICE OF TECHNOLOGY; GUIDING CRITERIA; REFERENCES; Chapter 9. Water and Sanitation: Cultural Considerations; BELIEF SYSTEMS REGARDING SANITATION AND DISEASE; CULTURAL FACTORS IN COMMUNITY PARTICIPATION; RECOMMENDATIONS FOR PROJECT SUCCESS; CONCLUSION; REFERENCES; Chapter 10. Training People to Meet the Global Need; THE GLOBAL NEED; WHO AND WHY?; HOW MANY NEED TRAINING?; WHAT KIND OF TRAINING?; TRAINING OF POLICYMAKERS.